Affordable Fourth Industrial Revolution Tools to Enhance Subsistence Farming: A Case Study of Small-Scale Farmers in KwaDlangezwa, KwaZulu-Natal, South Africa - Mtshali, Thabisile Luyanda (Journal of Cultural Analysis and Social Change, 2026)
Subsistence farming remains critical to rural livelihoods and food security in South Africa, yet farmers face persistent challenges including climate variability, resource constraints, and limited market access. The Fourth Industrial Revolution (4IR) presents opportunities to transform subsistence agriculture through affordable technologies such as IoT sensors, mobile advisory platforms, solar-powered irrigation, and digital marketplaces. However, high costs, infrastructure deficits, and digital literacy gaps hinder adoption among resource-constrained farmers. This qualitative case study explores the current farming practices, challenges, and potential for 4IR technology adoption among subsistence farmers in KwaDlangezwa, KwaZulu-Natal. Through semi-structured interviews with ten experienced farmers and thematic analysis of their narratives, the study identifies eight key themes: traditional farming practices, economic constraints, infrastructure challenges, digital literacy barriers, perceived technology inappropriateness, marketing strategies, climate adaptation, and institutional support gaps. Findings reveal a significant reality-technology gap, where commercially-designed 4IR tools remain inaccessible for subsistence contexts. The study recommends phased implementation strategies, government subsidies, digital literacy training, infrastructure development, and context-specific technology design to facilitate inclusive 4IR adoption. These findings contribute to sustainable development goals (SDGs 1, 2, 8, and 12) and provide practical pathways for enhancing agricultural productivity while acknowledging traditional knowledge systems.